Geriatric Insomnia - Hadilofyani, Putri Deas; Rose Dina Martini (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Insomnia is one of the most prevalent sleep disorders in the geriatric population and is considered a geriatric syndrome with substantial effects on physical, cognitive, and psychosocial health. Age-related changes in sleep architecture and circadian rhythms, along with an increased burden of chronic diseases and psychosocial factors, contribute to the high prevalence of insomnia among older adults. This condition is associated with an increased risk of depression, cognitive decline, cardiovascular and metabolic diseases, decreased quality of life, and higher morbidity and mortality. Therefore, an in-depth understanding of insomnia in geriatric patients is essential for effective clinical management. This study employed a literature review design, analyzing relevant scientific publications on insomnia in older adults. Sources included textbooks, clinical practice guidelines, and recent peer-reviewed journal articles discussing definitions, epidemiology, risk factors, pathophysiology, diagnostic methods, and management strategies. The findings indicate that insomnia in older adults is multifactorial, influenced by biological, psychological, and social factors, as well as comorbid medical conditions and polypharmacy. Diagnosis is primarily based on comprehensive clinical history taking, supported by validated assessment tools such as the Insomnia Severity Index (ISI) and the Pittsburgh Sleep Quality Index (PSQI), along with evaluation of underlying medical and psychiatric conditions. Nonpharmacological interventions are recommended as first-line therapy, particularly Cognitive Behavioral Therapy for Insomnia (CBT-I), sleep hygiene education, stimulus control, sleep restriction, and bright light therapy. Pharmacological treatment may be considered cautiously, given age-related pharmacokinetic changes and the heightened risk of adverse effects, including falls, cognitive impairment, and drug dependence. In conclusion, insomnia in the geriatric population is a complex condition requiring comprehensive assessment and a strong emphasis on nonpharmacological management to ensure safe and effective outcomes.